Evaluación y estudio del sistema de agua potable y alcantarillado sanitario y pluvial de los barrios Los Esteros, Nueva Esperanza, Sauces I, Sauces II sector 4, Sauces II sector 6, Justicia Popular, San Eduardo, perteneciente al cantón Machala, provincia de El Oro. - Pesántez Gía, Julio Armando (2015)
In the city of Machala, the Jubones parish where they are seated sites Los Esteros, New Hope, Sauces I, Sauces II Sector 4, Sauces II Sector 6, Justice People, San Eduardo, places which has done is this investigation, which was verified not have the services of sanitary and storm sewers, and have a water service, which was evaluated and do not meet the pressures and speeds necessary for the water supply of the people . The methodology used this project would be exploratory study, experimental and field type since information is based on literature, internet, books, and field data. The characteristics of the research project and obtained the need for a new water system and distribution network are determined, for which we rely on the rules INEN CPE 5 Part 9-1: 1992, a closed network was raised to balance the pressures and speeds, designing with PVC pipe U / Z 1 Mpa. For the design of sanitary sewer and storm CPE rules were applied INEN 5 Part 9-1: 1992, using network design PVC pipes minimum of 200 and 250 mm storm sewer, once obtained medical calculations arises a system of wastewater treatment with Anaerobic reactors with upflow sludge Hypochlorinator mantles and rain water system that flows into the canal El Macho.